Exploring an Institutional Base: Locating a Queer Women's Community in Thunder Bay, Ontario, Canada - Sullivan, Rachael (Atlantis)

(untitled) (Mount Saint Vincent University, 2009)
This article explores how an institutional base is created by lesbian, bisexual, and queer women living in the rural Canadian city of Thunder Bay, Ontario. Issues of access, exclusion, and use of the local university queer resource centre as a key site for community building figure prominently in the article.